O curso de licenciatura interdisciplinar em ciências humanas/Campus de Imperatriz: a interdisciplinaridade na formação de professores - PINTO, Josenilde Meireles (2020)
This Master's Dissertation is part of the Research Group “School, Curriculum and Teacher Training”, of the Graduate Program in Education at the Federal University of Maranhão. We analyzed the training of teachers in the perspective of interdisciplinarity developed in the Interdisciplinary Degree Course in Human Sciences to support teaching practice. The methodological approach that guides this study is qualitative, as it allows an interpretative analysis, involving the multiple determinations of the investigated object and allows the understanding of the phenomena from the perception of the investigated subjects, fundamental to understand the process of teaching practice towards Interdisciplinarity relying on Severino (1995), Bogdan and Biklen (1994), Minayo (2010), and others. The data collection techniques and instruments applied were bibliographic and documentary research, followed by field observation and semi-structured interviews with teachers, students and coordinator of the Interdisciplinary Degree Course in Human Sciences / Campus Imperatriz. The research consisted of 10 teachers, one of whom was the Course Coordinator and 09 students from the final periods, totaling 19 subjects surveyed and the categories of analysis were: Teacher training and Interdisciplinarity. The theoretical basis we supported was the work of Saviani, 2009, Tanuri (2000, Kuenzer (1999, Freitas (2014), Tardif, Lessard and Gauthier (2002), Ghedin (2002), Gómez (1995, Schõn (1995) Diniz -Pereira (2007; 2014): Lenoir (2006), Gusdorf (2006), Klein (1998), Japiassu (1976), Fazenda (2011), among other scholars of these themes, in addition to analyzing documents such as laws, the Pedagogical Political Project Course and Course Regulations. According to the analyzes, it was found that the concept of teacher training developed in the Interdisciplinary Degree Course in Human Sciences - Campus de Imperatriz revealed to be largely directed to the model of technical rationality, which gives the teacher the execution of tasks by technical and instrumental means in achieving results. On the other hand, there was also a coexistence with the concept of critical education, aligned with the critical rationality model, which presents a reflexive perspective of educational processes and their teaching practice. We note that although teachers and students consider Interdisciplinarity as a need to obtain broader knowledge and as a dialogue between different areas of knowledge, we note that the individualized process of their teaching practice has hindered the development of Interdisciplinarity in teaching practice. In this sense, they recognize the importance of the collective planning and seek to create efforts so that this practice can occur in the teaching- learning process. Thus, it is necessary to recognize that the development of Interdisciplinary actions implies collective practice, the basis of which is centered on the critical dimension of teacher education. Therefore, teachers and students, when understanding Interdisciplinarity as a possibility to rescue a broader formation, it is necessary to break with the established individualism.